Analgesic Rescue With Opioid-Only Thoracic Epidural After Surgical Infiltration of Liposomal Bupivacaine: A Case Report. Issue 8 (15th October 2019) - Swisher, Matthew W.; Millar, Melissa B.; Gabriel, Rodney A.; Said, Engy T.
Abstract : We present the case of a 51-year-old man with a history of recurrent lung cancer after left upper lobectomy who presented for an elective completion pneumonectomy via a bilateral anterior thoracotomy incision. At the completion of surgery, bilateral multilevel intercostal infiltration was performed with liposomal bupivacaine. Due to poorly controlled postoperative pain after extubation, a thoracic epidural was placed in the intensive care unit. An opioid-only infusion was started and transitioned to a local anesthetic–based infusion on postoperative day 2. This case report represents a novel stepwise approach of thoracic epidural management after surgical infiltration of liposomal bupivacaine.